2014
DOI: 10.1111/clr.12364
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: New bone formation in bone defects after melatonin and porcine bone grafts: experimental study in rabbits

Abstract: Melatonin has proven to regenerate the width and length of cortical bone in tibiae rabbits more quickly than collagenized porcine bone. Melatonin acts as a bone stimulator compared with porcine bone and control sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The use of melatonin to promote bone regeneration in dental implant placement was assessed in several studies, based on different animal models in which the authors employed melatonin alone or in combination with other substances, such as, growth hormone or porcine bone [2,40,41,42,43,44,45,46,47]. The studies using melatonin to promote dental implant stability evaluated in this review are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The use of melatonin to promote bone regeneration in dental implant placement was assessed in several studies, based on different animal models in which the authors employed melatonin alone or in combination with other substances, such as, growth hormone or porcine bone [2,40,41,42,43,44,45,46,47]. The studies using melatonin to promote dental implant stability evaluated in this review are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, significant osteoid matrix synthesis and mineralization accelerated early cell differentiation. It was observed to increase (Calvo-Guirado et al, 2015).…”
Section: Resultsmentioning
confidence: 91%
“…Besides, MLT was given to CD-1 mice but not to Sprague-Dawley rats in the study of Histing et al [28]. Moreover, It is uncertain that whether MLT regulates NPY and NPY1R expression via MLT receptors because MLT can work by both receptor-dependent and -independent mechanisms [29,30]. Previous studies showed that the level of NPY was increased by MLT treatment [31,32].…”
Section: Discussionmentioning
confidence: 99%